(3GdSQ GdecJhe aj Yde Gdadc hGdfLhes - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3agPG GdcJGH jLeY ajg edNU eG hUd EdjfG ef Yde GdWdeSGJ hGdSMQjGJ hGdYRGFe hOYhI GdchGcH s
(3BNQgG (B:s
(3hEjGce CjgG GdENhGf GdeNdUhf Cf JchfhG gcPG s
(3ajgG HYV GdQShe GdSMQjI heYOhOI HGdCQbGe GdEaQfLjgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B507 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B63 s
Keywords: (3Gdadcs